Development of a Pediatric PICC Team Under an Existing Sedation Service: A 5-Year Experience. (October 2019) - Rainey, Shane C; Deshpande, Girish; Boehm, Haley; Camp, Kim; Fehr, Annette; Horack, Kimberly; Hanson, Keith
Objective: To examine our institutional experiences with ultrasound-guided peripherally inserted central catheter (US-PICC) placement by a dedicated US-PICC team under the umbrella of an existing pediatric sedation service. Methods: Retrospective review of quality data examining 968 US-PICC encounters over a 5-year period from 2012 to 2016. Data for each encounter included line indications, success rate, dwelling time, need for sedation, and incidence of complications including venous thrombosis, infection, and accidental removal. Results: US-PICC lines were successfully placed in 89% of patients with an average age of 5.4 years. Extended antibiotic treatment was the most common indication for US-PICC placement and the mean dwell time was 23 days. Long-term complications were noted in 6.1% of cases, with venous thrombosis and line infection complicating 1.7% and 0.9% of encounters, respectively. Conclusion: Results suggest that our endeavor of creating a dedicated US-PICC team under an existing pediatric sedation service is successful with regard to the number of lines placed, success rates, and incidence of complications. This approach may be beneficial to other institutions seeing to maximize resource utilization and streamline patient care.